Efficacy and safety of Guben Tongluo formula in treating chronic kidney disease (stage G3): a multicenter randomized controlled clinical trial - Duan, Lianxiang; Liu, Ziyang; Chen, Ling; Yang, Yiqing; Fan, Yenan; Chen, Jie; Hu, Jing; Gong, Xuezhong; Guo, Yue (Frontiers in Medicine, 2025)
BackgroundThe incidence of chronic kidney disease (CKD) is increasing yearly; however, an effective drug treatment method for early-stage CKD (stage G3) is lacking. Thus, we aimed to determine the efficacy and safety of Guben Tongluo formula (GTF) for patients with CKD (stage G3).MethodsOne hundred and twenty participants were enrolled and randomly divided into losartan potassium (LP) group and LP + GTF group. LP group received general treatments combined with LP, and LP + GTF group received general treatments combined with GTF and LP. Evaluation indicators included changes in renal function, serum lipid, inflammatory factors, oxidative damage, renal fibrosis, traditional Chinese medicine (TCM) symptom scores, and clinical effective rate. In addition, vital sign indicators and adverse events (AEs) were closely observed throughout the study.ResultsScr and BUN levels were significantly lower and eGFR were significantly improved in LP + GTF group (p < 0.05). There was no statistically significant difference of UA and 24 h U-pro levels (p > 0.05). TG, TC levels were significantly lower and HDL-C levels were significantly higher in LP + GTF group (p < 0.01). No statistically significant difference in LDL-C levels was observed (p > 0.05). Inflammatory factors levels were significantly lower in LP + GTF group (p < 0.01). Notable increases in HO-1 and SOD levels were observed in LP + GTF group (p < 0.01), and MDA levels showed no statistically significant difference (p > 0.05). CTGF and TGF-β1levels were significantly lower in LP + GTF group (p < 0.01), while no significant difference was observed of PC-III and Col-IV levels (p > 0.05). TCM syndrome scores in LP + GTF group were significantly lower (p < 0.01). The clinical efficiency rate in LP + GTF group (73.3%) was better than that in LP group (40%). No significant between-group differences were observed in AEs.ConclusionLP + GTF group demonstrated a better clinical efficacy rate than LP group. GTF regulates serum lipid levels and has anti-inflammatory, antioxidative, and anti-renal fibrosis effects. GTF showed potential benefits in this small multicenter randomized controlled trial, warranting confirmation in larger, fully blinded randomized trials.